Māori values for Māori business: Cultural Capital in Indigenous Organisations - Best, Philip; Love, Matene (School of Management Working Papers, 2010)
Cultural capital holds much prospect as a theoretical concept for engaging core Indigenous Māori values in capitalistic endeavours, yet it still awaits satisfactory interpretation by Indigenous Māori management theorists researching in Aotearoa New Zealand. Particularly, little is known about how Māori values, beliefs and perspectives impact managerial decision making to create competitive advantage locally, nationally and internationally. Kaupapa Māori Research has been cited in the research literature as an ideal method for exploring the little known experiences of Māori managers employing the concept of cultural capital. This paper argues that a particular variation of Kaupapa Māori Research be employed to collect and interpret empirical material collected in face-to-face interviews with managers in Māori centred (tribal and family-based) organisations operating in Aotearoa New Zealand.